Composite bipolar plate for fuel cell and preparation method and application thereof
By forming a dense alloy layer of chromium, iron, nickel, aluminum and other elements on the surface of the stainless steel bipolar plate, the problems of corrosion resistance and insufficient thermal conductivity of the fuel cell bipolar plate are solved, and a longer service life and better Fuel cell performance.
Patent Information
- Application Number
- CN202210914921.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-08-01
AI Technical Summary
The existing fuel cell bipolar plates have shortcomings in corrosion resistance and thermal conductivity, especially the metal bipolar plates cannot meet the requirements of fuel cells for corrosion performance. At the same time, traditional chrome penetration processes have safety hazards and surface roughness problems.
An alloy layer is formed on the surface of the stainless steel bipolar plate. The alloy layer contains elements such as chromium, iron, nickel, aluminum, etc. It forms a dense alloy layer at high temperature through vacuum infiltration, which increases corrosion resistance and covers the bipolar plate to extend its use life.
The high corrosion resistance and good thermal conductivity of the bipolar plate are achieved, which avoids corrosion and heat accumulation problems, extends the service life of the bipolar plate, and improves its application in fuel cells.
Smart Images

Figure CN115275251B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bipolar plates, and in particular to a composite bipolar plate for a fuel cell and a preparation method and application thereof. Technical Background
[0002] Fuel cell bipolar plates, also known as flow field plates, are stacked with membrane electrode layers to form a fuel cell stack, which supports, collects current, provides channels for coolant, and separates oxidants and reductants in fuel cells. At the same time, bipolar plates must also have good heat dissipation performance, strong corrosion resistance, and good shock resistance.
[0003] The bipolar plates commonly used in fuel cells include graphite carbon plates, metal bipolar plates, and composite bipolar plates. At present, the most mature and widely used are graphite carbon plates. However, graphite carbon plates have problems such as thick thickness and poor seismic performance. They can only be installed in fuel cell stacks of large vehicles such as public transportation and heavy trucks, and cannot be used in ordinary small passenger cars.
[0004] Metal bipolar plates can be made by stamping stainless steel sheets, and have a series of advantages such as low thickness, light weight, good shock resistance, and low price. However, pure stainless steel bipolar plates cannot meet the corrosion performance requirements of fuel cells for bipolar plates, which is the biggest problem limiting the use of metal bipolar plates.
[0005] Chromium, as the main anti-corrosion alloy element in metals such as stainless steel and high-temperature alloys, has extremely strong corrosion resistance. Diffusion of a chromium layer on the surface of stainless steel will improve its corrosion resistance by dozens of times. At the same time, the electrical conductivity and thermal conductivity of chromium are better than those of stainless steel. After diffusion of a chromium layer on the surface of stainless steel, the overall thermal conductivity and electrical conductivity of the stainless steel bipolar plate will not decrease. The traditional stainless steel surface chromizing process adds ammonium chloride as a catalyst, which will cause the surface of the parts to become sticky and rough, and ultimately make the surface finish of the parts unable to meet the use requirements. At the same time, ammonium chloride decomposes a large amount of ammonia and hydrogen chloride gas, and the chromizing process is prone to safety accidents. Summary of the invention
[0006] In view of the above-mentioned technical limitations, the present application proposes a composite bipolar plate for a fuel cell and a preparation method thereof; the present application forms an alloy layer by performing surface treatment on the area close to the surface of the stainless steel, and the alloy layer is embedded in the structure of the original bipolar plate. The substances in the alloy layer cooperate with each other to form a structure with good density, which can prevent the bipolar plate from being corroded; in addition, an oxide layer is formed on the outside, which can coat the bipolar plate, further protect the bipolar plate, and extend the service life of the bipolar plate.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] The invention of the present application is to provide a composite bipolar plate for a fuel cell, wherein the surface of the composite bipolar plate contains an alloy layer; by mass, the alloy layer includes 30% to 95% chromium, 3% to 45% iron, 1% to 10% nickel, 0.5% to 5% aluminum, and 0 to 5% trace metal elements.
[0009] Optionally, the alloy layer has a thickness of 0.1 μm to 20 μm.
[0010] Optionally, the substrate of the composite bipolar plate is stainless steel.
[0011] Optionally, the substrate of the composite bipolar plate includes at least one of 304 stainless steel, 304L stainless steel, 310 stainless steel, 310L stainless steel, 316 stainless steel, 316L stainless steel, and 347 stainless steel.
[0012] Another inventive point of the present application is to provide a method for preparing a composite bipolar plate.
[0013] Optionally, the preparation method comprises: (1) obtaining a stainless steel bipolar plate; (2) embedding the stainless steel bipolar plate in a surface treatment agent under vacuum conditions, performing surface treatment, and obtaining the composite bipolar plate.
[0014] Optionally, the surface treatment agent includes 20 to 60 parts of chromium, 30 to 70 parts of a dispersant, 0.1 to 5 parts of a reducing agent, and 0.5 to 5 parts of an activator.
[0015] Optionally, the vaporization temperature of the reducing agent is lower than the alloying temperature; the vaporization temperature of the activating agent is lower than the alloying temperature; and the activating agent contains halogen.
[0016] Preferably, the reducing agent comprises a magnesium-aluminum eutectic alloy; the activating agent comprises zinc chloride; and the dispersing agent comprises at least one of aluminum oxide, silicon oxide and magnesium oxide.
[0017] Optionally, the vacuum refers to a vacuum degree less than 13 Pa; the alloying conditions are: temperature 917-1050° C., time 3-10 hours.
[0018] Another inventive point of the present application is to provide an application of the composite bipolar plate as described above in a fuel cell.
[0019] Compared with the prior art, this application has the following advantages:
[0020] (1) The composite bipolar plate for fuel cells of the present application is surface treated in the area near the surface of the stainless steel, so that the chromium and aluminum elements are embedded into the surface of the bipolar plate and become part of the bipolar plate. There is no interface problem between different metals, thereby effectively avoiding problems such as coating shedding. The embedding of chromium and aluminum elements can fill the gaps between the original bipolar plate substrates, making the structure denser, avoiding subsequent erosion of the bipolar plate, and extending its service life. In addition, the thickness of the generated composite bipolar plate is not much increased compared to the original bipolar plate. Only the bipolar plate is slightly expanded due to the embedding of the metal, thereby avoiding the limitation of the application of the bipolar plate in fuel cells due to excessive thickness.
[0021] (2) The preparation method of the composite bipolar plate in the present application is to perform surface treatment on the bipolar plate by vacuum infiltration. The reducing agent is vaporized under a certain vacuum and temperature. The vaporized reducing agent vapor will quickly react with various oxides (including the oxide film on the surface of the bipolar plate substrate and the oxide film on the surface of the raw material, etc.), remove the oxygen in the surface oxide film layer to form oxides, which are then extracted under continuous vacuum conditions, thereby exposing elements such as chromium and aluminum, laying the foundation for subsequent infiltration; the activator is also vaporized under this condition and becomes a gas state. The gaseous activator provides a large amount of active chloride ions, which accelerates the reaction and makes the chromized layer generated by the reaction dense and smooth. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an optical microscope image of the magnesium-aluminum eutectic alloy used in Experimental Example 1 of the present application;
[0023] Figure 2 This is an optical microscope image of the magnesium-aluminum eutectic alloy after magnesium evaporation used in Experimental Example 1 of the present application;
[0024] Figure 3 AES diagram of the distribution of different elements with depth in the composite bipolar plate provided in Experimental Example 1 of this application; the ordinate is distance, in μm; the abscissa is electron intensity, without unit;
[0025] Figure 4 A scanning electron microscope image of the surface of the composite bipolar plate provided in Experimental Example 1 of this application;
[0026] Figure 5 A scanning electron microscope image of a cross section of a composite bipolar plate provided in Experimental Example 4 of the present application;
[0027] Figure 6 The finished product image of the composite bipolar plate surface provided in Experimental Example 1 of this application;
[0028] Figure 7 This is a finished picture of the surface of the composite bipolar plate provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.
[0030] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application, and the terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.
[0031] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.
[0032] Example 1
[0033] The present embodiment provides a composite bipolar plate for a fuel cell, wherein the surface of the composite bipolar plate contains an alloy layer; the alloy layer includes, by mass, 30% to 95% chromium, 3% to 45% iron, 1% to 10% nickel, 0.5% to 5% aluminum, and 0 to 5% trace metal elements.
[0034] The chromium content in stainless steel is generally less than 30%. When the chromium content is less than 30%, it is difficult to form a sufficiently dense chromium passivation film, so it cannot have a sufficient protective effect. In the composite bipolar plate of the present application, there is a chromium alloy layer, and the chromium content in the alloy layer is ≥30%, which is the main element in the alloy layer, so that chromium and chromium can be connected to form a sufficiently dense passivation film; and it is also doped with aluminum. Chromium and iron are body-centered cubic structures, while aluminum is a face-centered cubic crystal with a tighter stacking method. The addition of aluminum can fill the gaps between chromium and iron, and through structural space control, the slippage of nickel and aluminum is avoided, so that the entire structure is in a stable state, and external gases or solvents are avoided from entering the structure, so that it has better corrosion resistance.
[0035] It has high corrosion resistance in acidic or alkaline environments, which can extend the service life of the composite bipolar plate; it improves high temperature resistance and can maintain its original shape without deformation during subsequent use.
[0036] The trace metal elements include any one of molybdenum, manganese, vanadium, titanium, cobalt and barium.
[0037] The thickness of the chromium alloy layer is 0.1μm to 20μm, for example, it can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value between any two values.
[0038] If the thickness is less than 0.1 micron, it is difficult to form a completely continuous alloy layer. Once the alloy layer is discontinuous, gaps will appear in the alloy layer, allowing acidic substances to enter the bipolar plate, causing corrosion of the substrate and making the bipolar plate unable to function normally. If the thickness is greater than 20 microns, on the one hand, the surface brittleness will increase rapidly, resulting in a decrease in the toughness of the overall material. On the other hand, too thick an alloy layer will affect the conductivity in the fuel cell.
[0039] The base material of the composite bipolar plate is stainless steel.
[0040] The substrate of the composite bipolar plate includes at least one of 304 stainless steel, 304L stainless steel, 310 stainless steel, 310L stainless steel, 316 stainless steel, 316L stainless steel, and 347 stainless steel.
[0041] The main component of stainless steel is iron, which has good compatibility with chromium and aluminum to form chromium-iron-aluminum alloy.
[0042] Example 2
[0043] This embodiment provides a method for preparing a composite bipolar plate. The composite bipolar plate is the same as the composite bipolar plate in Embodiment 1, and therefore will not be described in detail here.
[0044] The preparation method comprises: (1) obtaining a stainless steel bipolar plate; (2) embedding the stainless steel bipolar plate in a surface treatment agent under vacuum conditions, performing surface treatment, and obtaining the composite bipolar plate.
[0045] The stainless steel bipolar plate in step (1) can be commercially available, or can be prepared by the following method: according to the design of the internal space flow channel structure of the bipolar plate, a stainless steel plate is processed by a stamping process to obtain a stainless steel bipolar plate.
[0046] Step (2) comprises: under vacuum conditions, at least one side of the stainless steel bipolar plate is covered with a surface treatment agent and subjected to surface treatment to obtain the composite bipolar plate.
[0047] The surface treatment agent is in powder form. If there are lumps or large particles in the surface treatment agent, it needs to be ground into powder before use. Small particles of powder help the surface treatment process to occur more evenly and can promote the fusion of alloy and stainless steel faster and more.
[0048] The particle size of the surface treatment agent is less than 50 mesh, preferably 80 to 200 mesh. This range can ensure that the powder can fully contact and react with the stainless steel surface, and can also avoid the powder itself from being easily sintered and agglomerated due to the particle size being too fine, which affects the use.
[0049] The surface treatment agent comprises 20 to 60 parts of chromium, 30 to 70 parts of dispersant, 0.1 to 5 parts of reducing agent and 0.5 to 5 parts of activating agent by mass. Among them, chromium can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two values; the dispersant can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts or any value between any two values; the reducing agent can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two values; the activator can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or any value between any two values.
[0050] Optionally, the vaporization temperature of the reducing agent is lower than the alloying temperature; the vaporization temperature of the activating agent is lower than the alloying temperature; and the activating agent contains halogen.
[0051] Preferably, the vaporization temperature of the reducing agent is not less than the vaporization temperature of the activating agent.
[0052] More preferably, the vaporization temperature of the reducing agent is lower than the vaporization temperature of the activating agent.
[0053] Preferably, the reducing agent comprises a magnesium-aluminum eutectic alloy; the activating agent comprises zinc chloride; and the dispersing agent comprises at least one of aluminum oxide, silicon oxide and magnesium oxide.
[0054] Optionally, the vacuum refers to a vacuum degree less than 13 Pa; the alloying conditions are: temperature 917-1050° C., time 3-10 hours.
[0055] Under the condition of a vacuum degree of 13 Pa, the vaporization temperature of chromium is 917° C., and chromium will vaporize when the temperature of the alloy treatment is greater than or equal to 917° C. Preferably, the temperature of the alloy treatment is 917° C. to 1150° C., and the time is greater than 2 hours.
[0056] The chromizing process is carried out at a temperature greater than 917°C. At this time, chromium has a body-centered cubic structure with an atomic radius of 0.1249nm, and free iron ions have a face-centered cubic structure with an atomic radius of 0.1288nm. The atomic radii of chromium and iron at high temperatures are relatively close. Under high temperature conditions, chromium and iron are easy to form a substitutional solid solution. As the insulation time increases, chromium continues to penetrate, and the chromium content continues to increase. At the same time, aluminum can be transformed into aluminum with a high surface ratio and high activity as magnesium vaporizes, and the oxide film attached to the aluminum surface is removed, further promoting the activity of aluminum. Aluminum has a face-centered cubic crystal structure, and its atomic radius is relatively close to that of chromium and iron; and at this high temperature, aluminum can melt and form a certain "molten mixture" with chromium and iron, and then, under the action of active chloride ions, it and chromium diffuse and alloy with stainless steel.
[0057] After the chromizing is completed, the iron will transform from a face-centered cubic structure to a body-centered cubic structure during the cooling process, and the volume will expand. Due to the "anchoring" effect of chromium atoms at this time, the volume expansion during the cooling process is limited, and the final chromized layer structure is a uniform and dense structure, which can prevent water and water vapor from penetrating into the matrix and reacting with the free iron ions in the matrix, and has good corrosion resistance. At the same time, since aluminum is a good conductor of heat, its thermal conductivity is 3 times greater than that of iron, so the addition of aluminum elements can make the prepared bipolar plates have better heat dissipation function.
[0058] Magnesium aluminum alloy powder is a eutectic powder. Figure 1 As shown, its melting point is much lower than that of elemental magnesium and aluminum. It starts to melt at about 450°C. Under vacuum conditions less than 13Pa, the magnesium in the magnesium-aluminum alloy starts to vaporize at about 450°C. Since the vaporization temperature of aluminum is as high as 1200°C under this vacuum condition, aluminum will not vaporize. On the one hand, the vaporized magnesium reacts with the oxygen on the surface of aluminum, exposing the highly active aluminum. At the same time, a large number of holes will be left after the magnesium in the powder vaporizes, such as Figure 2 As shown, the specific surface area of the powder is greatly increased, accelerating the infiltration of aluminum. On the other hand, the vaporized magnesium reacts with the chromium oxide on the surface of chromium, taking away the chromium oxide film that would hinder the chromization process. Under the catalytic action of active chloride ions, chromium and aluminum simultaneously infiltrate into the nickel matrix.
[0059] In addition, aluminum has a certain reducing property. During the chromizing process, aluminum will react slightly with the chromium surface, and the reaction process is an exothermic reaction. This process can promote the infiltration of chromium while also causing a certain amount of aluminum to penetrate. A small amount of aluminum in the infiltration layer can improve the comprehensive corrosion resistance of the infiltration layer, mainly because aluminum can make the infiltration layer dense.
[0060] Preferably, the surface treatment process is divided into three stages. The first stage is the vaporization of the reducing agent, that is, the temperature of the first stage needs to reach or exceed the vaporization temperature of the reducing agent; the second stage is the vaporization of the activating agent, and the temperature of the second stage needs to reach or exceed the vaporization temperature of the activating agent; the third stage is the alloying temperature, that is, it needs to reach or exceed the vaporization temperature of chromium.
[0061] Preferably, the temperature of the first stage is 450-500°C; the temperature of the first stage is 750-850°C; the temperature of the first stage is 917-1050°C.
[0062] Aluminum is a powder of magnesium-aluminum eutectic alloy (in which aluminum accounts for 45wt% to 55wt%), the melting point of which is about 450℃, which is lower than the melting points of the components aluminum and magnesium, and more active. After the magnesium and aluminum are melted, the magnesium in it becomes gaseous as the temperature rises, which not only reduces the chromium oxide film on the surface of the chromium powder, but also provides active aluminum, ensuring that the aluminum also penetrates into the matrix while the chromium penetrates.
[0063] In the first stage, the temperature is slowly increased, and the heating rate is preferably less than 5°C / min, so that the magnesium in the magnesium-aluminum alloy is fully vaporized, the oxide film is broken, and by-products are generated. These by-products are removed as the vacuum is drawn, and active aluminum is produced at the same time. In the second stage, the heating rate is less than 10°C / min to prevent the activator from being quickly drawn away, to maximize contact with chromium, and to activate the chromium to generate active ions. The third stage is alloying, so that the activated chromium, nickel and aluminum are alloyed with stainless steel to form a dense alloy layer.
[0064] When the reducing agent is within the vacuum condition and temperature range, the reducing agent has already vaporized, that is, the vaporization temperature of the reducing agent is lower than the above temperature under the above vacuum condition. The activating agent is a substance that can release active chloride ions, preferably a substance that can vaporize under the above vacuum condition and temperature range, thereby releasing active chloride ions.
[0065] The dispersant includes at least one of aluminum oxide, silicon oxide, and magnesium oxide; the reducing agent includes a magnesium-aluminum eutectic alloy; and the activating agent includes zinc chloride.
[0066] Under 13Pa vacuum conditions, the vaporization temperature of chromium is 917℃, and this phenomenon can be used to perform chromization treatment under vacuum conditions. However, due to the dense chromium oxide film on the surface of the chromium powder (particles), the chromium powder (particles) cannot be vaporized under this condition. Even if the vacuum degree and temperature are further increased, it is still difficult to achieve the vaporization of the chromium powder (particles). Under 13Pa vacuum conditions, the vaporization temperature of magnesium is 439℃. The vaporized magnesium vapor will quickly react with the chromium powder (particles), remove the oxygen in the chromium oxide film on the surface of the chromium powder (particles) to form magnesium oxide, which is then pumped away under continuous vacuum conditions. The boiling point of zinc chloride is 732℃, and gaseous zinc chloride provides a large amount of active chloride ions, which accelerates the reaction.
[0067] More preferably, the alloy temperature is treated in stages, firstly raised to 450°C, then slowly raised to 732°C (vaporization temperature of zinc chloride), and then slowly raised to 917°C to 1150°C, to avoid rapid extraction of zinc chloride and magnesium vapor.
[0068] Example 3
[0069] According to the content of this application, the preparation method of the composite bipolar plate for fuel cells of Example 1 and the composite bipolar plate of Example 2 is specifically described, and the specific description is as follows:
[0070] Test Example 1
[0071] (1) Obtain a stainless steel bipolar plate; purchase 100 μm thick 304 stainless steel from the market and process or stamp it into the required shape.
[0072] (2) The stainless steel bipolar plate is embedded in an 80-mesh surface treatment agent, wherein the surface treatment agent includes: 26 parts of chromium powder, 45 parts of silicon oxide, 2 parts of magnesium-aluminum eutectic alloy (of which aluminum accounts for 45wt%), and 3.6 parts of zinc chloride. Then, vacuum is evacuated. When the vacuum degree reaches 13 Pa (the vacuum degree is maintained throughout the process), the temperature is increased at a rate of 2°C / min. When the temperature reaches 470°C, it is kept warm for 20 minutes; the temperature is increased at a rate of 4°C / min. When the temperature reaches 780°C, it is kept warm for 20 minutes; then the temperature is increased again at a rate of 2°C / min. When the temperature reaches 950°C, the temperature is stopped and maintained for 5 hours.
[0073] Afterwards, high-temperature shaping is performed at 880°C for 20 minutes to obtain the final composite bipolar plate.
[0074] Composition of the surface alloy layer: 66% chromium, 23% iron, 8% nickel, 2% aluminum, and the remainder of trace elements.
[0075] And if Figure 3 As shown, the morphology and element content of the cross section of the alloy layer are displayed (the ordinate is the distance to the surface, the larger the value, the farther from the surface; the abscissa is the electron intensity, the higher the intensity value represents the higher the element content). As the depth of the alloy layer increases, that is, the distance to the surface increases, the content of aluminum, chromium and iron elements remains unchanged within a certain range, indicating that the elements are evenly distributed in the alloy layer; the thickness of the alloy layer is about 12μm. At the interface between the alloy layer and the substrate layer, the content of aluminum and chromium drops sharply, and after entering the substrate layer, it gradually approaches zero; this indicates that the generated alloy layer can form a coating on the surface of the stainless steel substrate, protecting it from corrosion by water and gas, etc. At the same time, because it contains a certain amount of iron, it ensures continuity with the substrate and avoids interface problems; as shown Figure 4 As shown, the surface of the composite bipolar plate is dense, and the various substances cooperate with each other to form a dense surface without problems such as gaps, and can form a good protective effect.
[0076] Test Example 2
[0077] (1) Obtain a stainless steel bipolar plate; purchase 100 μm thick 304 stainless steel from the market and process or stamp it into the required shape.
[0078] (2) The stainless steel bipolar plate is embedded in a 180 mesh surface treatment agent, wherein the surface treatment agent includes: 58 parts of chromium powder, 68 parts of magnesium oxide, 5 parts of magnesium-aluminum eutectic alloy (of which aluminum accounts for 45wt%), and 1.8 parts of zinc chloride. Then, vacuum is evacuated. When the vacuum degree reaches 13Pa (the vacuum degree is maintained throughout the process), the temperature is increased at a rate of 3.5°C / min. When the temperature reaches 490°C, it is kept warm for 40 minutes; the temperature is increased at a rate of 6°C / min. When the temperature reaches 820°C, it is kept warm for 40 minutes; then the temperature is increased again at a rate of 3.5°C / min. When the temperature reaches 970°C, the temperature is stopped and maintained for 5 hours.
[0079] Afterwards, high-temperature shaping is performed at 880°C for 20 minutes to obtain the final composite bipolar plate.
[0080] The composition of the surface alloy layer is: 72% chromium, 18% iron, 6% nickel, 3% aluminum, and the remainder is trace elements. The thickness of the alloy layer is about 15μm.
[0081] Test Example 3
[0082] (1) Obtain a stainless steel bipolar plate; purchase 100 μm thick 304 stainless steel from the market and process or stamp it into the required shape.
[0083] (2) The stainless steel bipolar plate was embedded in a 95 mesh surface treatment agent, wherein the surface treatment agent included: 37 parts of chromium powder, 53 parts of silicon oxide, 3.5 parts of magnesium-aluminum eutectic alloy (of which aluminum accounted for 45wt%), and 4.5 parts of zinc chloride. Then, the plate was evacuated. When the vacuum degree reached 13Pa (the vacuum degree was maintained throughout the process), the temperature was raised at a rate of 4°C / min. When the temperature reached 480°C, the plate was kept warm for 30 minutes. The temperature was raised at a rate of 5°C / min. When the temperature reached 840°C, the plate was kept warm for 30 minutes. The plate was heated again at a rate of 4°C / min. When the temperature reached 985°C, the temperature was stopped and maintained for 6 hours.
[0084] Afterwards, high-temperature shaping is performed at 880°C for 20 minutes to obtain the final composite bipolar plate.
[0085] The composition of the surface alloy layer is: 75% chromium, 14% iron, 5% nickel, 4% aluminum, and the remainder is trace elements. The thickness of the alloy layer is about 18μm.
[0086] Test Example 4
[0087] (1) Obtain a stainless steel bipolar plate; purchase 100 μm thick 304 stainless steel from the market and process or stamp it into the required shape.
[0088] (2) The stainless steel bipolar plate is embedded in a 130 mesh surface treatment agent, wherein the surface treatment agent includes: 42 parts of chromium powder, 39 parts of aluminum oxide, 4.3 parts of magnesium-aluminum eutectic alloy (of which aluminum accounts for 45wt%), and 2.7 parts of zinc chloride. Then, vacuum is evacuated. When the vacuum degree reaches 13Pa (the vacuum degree is maintained throughout the process), the temperature is increased at a rate of 1.5°C / min. When the temperature reaches 460°C, it is kept warm for 50 minutes; the temperature is increased at a rate of 7°C / min. When the temperature reaches 790°C, it is kept warm for 50 minutes; then the temperature is increased again at a rate of 1.5°C / min. When the temperature reaches 920°C, the temperature is stopped and maintained for 7 hours.
[0089] Afterwards, high-temperature shaping is performed at 880°C for 20 minutes to obtain the final composite bipolar plate.
[0090] Surface alloy layer composition: 64% chromium, 24% iron, 8% nickel, 2% aluminum, and the remainder of trace elements. Figure 5 As shown, the thickness of the alloy layer in this test example is about 6 μm.
[0091] Test Example 5
[0092] (1) Obtain a stainless steel bipolar plate; purchase 100 μm thick 304 stainless steel from the market and process or stamp it into the required shape.
[0093] (2) The stainless steel bipolar plate is embedded in a 155 mesh surface treatment agent, wherein the surface treatment agent includes: 31 parts of chromium powder, 32 parts of magnesium oxide, 2.8 parts of magnesium-aluminum eutectic alloy (of which aluminum accounts for 45wt%), and 1 part of zinc chloride. Then, vacuum is evacuated. When the vacuum degree reaches 13 Pa (the vacuum degree is maintained throughout the process), the temperature is increased at a rate of 3°C / min. When the temperature reaches 455°C, it is kept warm for 25 minutes; the temperature is increased at a rate of 8°C / min. When the temperature reaches 810°C, it is kept warm for 25 minutes; then the temperature is increased again at a rate of 3°C / min. When the temperature reaches 1050°C, the temperature is stopped and maintained for 3 hours.
[0094] Afterwards, high-temperature shaping is performed at 880°C for 20 minutes to obtain the final composite bipolar plate.
[0095] The composition of the surface alloy layer is: 55% chromium, 30% iron, 9% nickel, 3% aluminum, and the remainder is trace elements. The thickness of the alloy layer is about 10μm.
[0096] Comparative Example 1
[0097] Only step (1) of Experimental Example 1 is included, that is, only the stainless steel bipolar plate is used without any surface treatment. Figure 6 and Figure 7 As shown, Figure 6 This is the finished product picture of Test Example 1 of this application. Figure 7 This is the finished product picture of comparative example 1. From the color observation, it can be seen that the bipolar plate of experimental example 1 is bright silver as a whole, and the surface is smooth and not rough; while the bipolar plate of comparative example 1 is matte, and it can be clearly seen that there are problems such as surface roughness.
[0098] Comparative Example 2
[0099] This comparison is a common graphite bipolar plate on the market. Graphite bipolar plate is the most commonly used bipolar plate in domestic proton exchange membrane fuel cells (PEMFC). It has good electrical conductivity, thermal conductivity, stability and corrosion resistance, but has relatively poor mechanical properties, is relatively brittle, and is difficult to machine, resulting in high costs.
[0100] The carbon powder or graphite powder is mixed with graphitizable materials, and after being pressed into shape by a machine, it is subjected to graphitization at a high temperature (usually 2200-2800°C) in a reducing atmosphere or under vacuum conditions; then, the graphite plate is impregnated and sealed, and the required gas flow channels are processed on its surface using a CNC machine tool.
[0101] Performance Testing
[0102] The composite bipolar plates of the test example and the comparative example were tested for parameters such as resistivity, compressive strength, contact resistance, corrosion current density and hardness. The test results are shown in Table 1.
[0103] Table 1
[0104] Test Example 1 Test Example 5 Comparative Example 1 Comparative Example 2 Bending strength of solar panels - - - 85.07 Shore hardness - - - 70.9 Shore Hardness 890HV 1080HV 220HV 88HV thickness 112μm 104μm 100μm 10mm Resistivity 0.98mΩ·mm 0.96mΩ·mm 1.02mΩ·mm 9.5mΩ·mm Compressive strength 723MPa 728MPa 711MPa 149.86MPa Contact resistance <![CDATA[2.1mΩ·cm 2 ]]> <![CDATA[1.8mΩ·cm 2 ]]> <![CDATA[98mΩ·cm 2 ]]> <![CDATA[6.74mΩ·cm 2 ]]> Corrosion current density <![CDATA[0.68μA·cm -2 ]]> <![CDATA[0.65μA·cm -2 ]]> <![CDATA[146μA·cm -2 ]]> <![CDATA[0.46μA·cm -2 ]]>
[0105] As shown in Table 1, the composite bipolar plates of Test Examples 1 and 5 of the present application have a significant improvement in Shore hardness compared to the bipolar plates of Comparative Examples 1 and 2, which is 3 to 11 times higher; from the perspective of the thickness of the bipolar plate, the stainless steel bipolar plate is thinner than the graphite bipolar plate and is suitable for more sophisticated electronic products; from the perspective of resistivity, the resistivity of the graphite bipolar plate is higher, while the stainless steel bipolar plate is only (1 / 9) to (1 / 10) of that of the graphite bipolar plate, which has a lower resistivity, indicating that the composite electrode plate of the present application has almost no effect on the conductivity of the bipolar plate; from the perspective of compressive strength, the range of the stainless steel bipolar plate is above 700 MPa, which is much greater than the 149 MPa of the graphite bipolar plate.
[0106] Generally speaking, at 140N·cm -2 Under the pressure of the fuel cell bipolar plate and the electrode gas diffusion layer, the interface contact resistance between the fuel cell bipolar plate and the electrode gas diffusion layer should be less than 10mΩ·cm 2 ; The contact resistance of the bipolar plate in Comparative Example 1 is too large, but the contact resistance after chromium and aluminum infiltration is significantly reduced and is much lower than that of the graphite bipolar plate, avoiding heat accumulation and causing harm and other problems.
[0107] In terms of corrosion current density, the composite bipolar plates of Test Examples 1 and 5 have a corrosion current density of 0.6 μA·cm -2 , which is much smaller than 146 μA·cm in Comparative Example 1. -2 ; And according to general conditions, when the corrosion current density is less than 1μA·cm -2 , indicating good corrosion resistance; while the values of Test Examples 1 and 5 of the present application are 0.6μA·cm -2 , less than 1μA·cm -2 , indicating that the composite bipolar plate after chromium and aluminum alloy has excellent corrosion resistance.
[0108] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a composite bipolar plate, wherein the surface of the composite bipolar plate comprises an alloy layer; the alloy layer comprises, by mass, 30% to 95% chromium, 3% to 45% iron, 1% to 10% nickel, 0.5% to 5% aluminum, and 0% to 5% trace metal elements, characterized in that: include: (1) obtaining a stainless steel bipolar plate; (2) Under vacuum conditions, the stainless steel bipolar plate is embedded in a surface treatment agent, and surface treatment is performed to achieve alloying, thereby obtaining the composite bipolar plate; the surface treatment agent comprises: by mass, 20 to 60 parts of chromium powder, 30 to 70 parts of a dispersant, 0.1 to 5 parts of a reducing agent which is a magnesium-aluminum eutectic alloy, and 0.5 to 5 parts of an activator.
2. The preparation method according to claim 1, characterized in that: The thickness of the alloy layer is 0.1 μm to 20 μm.
3. The preparation method according to claim 1, characterized in that: The substrate of the composite bipolar plate is stainless steel.
4. The preparation method according to claim 1, characterized in that: The substrate of the composite bipolar plate includes at least one of 304 stainless steel, 304L stainless steel, 310 stainless steel, 310L stainless steel, 316 stainless steel, 316L stainless steel, and 347 stainless steel.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The vaporization temperature of the reducing agent is lower than the alloying temperature; the vaporization temperature of the activating agent is lower than the alloying temperature; and the activating agent contains halogen.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The activator includes zinc chloride; the dispersant includes at least one of aluminum oxide, silicon oxide and magnesium oxide.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The vacuum refers to a vacuum degree less than 13 Pa; the alloying conditions are: temperature 917-1050° C., time 3-10 hours.
Citation Information
Patent Citations
Molten carbonate fuel cell
US5643690A
